The Effect of Motivation, Supervision and Transformational Leadership Style on the Implementation of Discharge Planning by Inpatient Unit Nurses - Agnesia; Rita, Kemala; Nofierni (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: Discharge planning is a particular service in ensuring the quality of hospital services. The motivation of Nurses, supervision by the head of nursing, and the role of leadership style contribute to discharge planning implementation. The purpose of this study was to analyze the effect of motivation, supervision, and transformational leadership style on the discharge planning implementation in inpatient unit nurses at XYZ Hospital, Bintaro Jaya. Research methods: This research is quantitative, and data collection is carried out using a questionnaire instrument. The number of samples determined was 106 inpatient unit nurses. The sampling technique was purposive sampling. The method of analysis using a multiple linear regression approach with the SPSS program is used for data analysis. The findings show that motivation has a significant and positive effect on discharge planning, supervision has a significant and positive effect on discharge planning, and transformational leadership style has a significant and positive effect on discharge planning. Recommendations for Hospital management should provide education and emphasis on nurses in the discharge planning process and compensation to encourage the motivation of nurses and increase the role of nurse managers as supervision/coaching and provide leadership training so that they can carry out their role optimally Keyword: Discharge Planning, motivation, supervision, leadership style